Multi-Parameter Laser Imaging Reveals Complex Microscale Biofilm Matrix in a Thick (4,000 μm) Aerobic Methanol Oxidizing Community - Lawrence, John R.; Winkler, Marcus; Neu, Thomas R. (Frontiers in Microbiology, 2018)
Although methanol has frequently been used as an inexpensive supplementary carbon source to support treatment processes, knowledge of the resultant microbial biofilms, their 3D architecture, microenvironments, exopolymer chemistry and populations remains limited. We supplied methanol as a supplementary carbon source to biofilms developing in rotating annular reactors. Analysis of circulation waters (1.0 l d-1) indicated that dissolved organic carbon was reduced by 25%, NO3-nitrogen by 95%, and total phosphorus by 70%. Analyses of populations using culture based techniques and fluorescence in situ hybridisation indicated enrichment of nitrifiers, denitrifiers and methylotrophic bacteria relative to reference biofilms not receiving methanol. The biofilms that developed were up to 4000 µm thick. Staining with fluor conjugated lectins in combination with nucleic acid stains, revealed the presence of discrete bacterial cells inside complex globular polymeric structures. These structures were in turn surrounded by an interstitial polymer containing a variety of bacterial cell types. The globular structures bound FITC-conjugated lectins, from Canavalia ensiformis and Ulex europeaus. The FITC-lectin of Phaseolus vulgaris bound the surface of the globular structures and more generally within the matrix. Chemical analyses of the polymer paralleled the results of lectin analyses indicating that the dominant neutral sugars were glucose, galactose, mannose, rhamnose, with fucose and ribose as minor constituents. Amino sugars were not detected. Dual channel imaging with pH sensitive probes indicated that pH gradients from pH 4 to 7 occurred across the globular microcolonies. Critically for the maintenance of aerobic conditions throughout the thick biofilm it was extensively penetrated by a fine fissure network revealed by the location of fluorescent latex microbeads as detected by confocal laser scanning microscopy. Microelectrode studies confirmed the absence of any detectable Eh gradients within the biofilm. However, mobility of various size-fractionated fluorescent probes indicated that the basal region was only penetrated by the lowest molecular weight probes with a hydrated radius of 2.2 nm or less. These observations indicate the selection of a unique, thick (>4000 m) microbial community in which a self-organized architecture promotes the maintenance of optimal conditions and metabolism throughout the biofilm community.